Hospital Legal Liability In Medical Dispute Resolution (Case Study Of South Jakarta District Court Decision Number 484/PDT.G/2013/PN.JKT.Sel) - Enina Wika Vetricha Wulandari; Handoyo Prasetyo; Handar Subhandi Bakhtiar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This research was conducted to determine the cause of negligence committed by medical personnel, and how to resolve medical disputes by analyzing the South Jakarta District Court Decision Number 484/Pdt.G/2013/PN.JKT.Sel. Further research was carried out by looking at the case related to the legal liability of hospitals for the negligence of their medical personnel by reviewing the Civil Code, Law Number 26 of 2009 concerning Health, Law Number 44 of 2009 concerning Hospitals, Law Number 29 of 2004 concerning the Practice of Medicine, Law Number 36 of 2014 concerning Health Workers, and other related laws and regulations. It then examines whether or not the judge is appropriate in deciding a malpractice case. This research uses normative juridical research with a statutory approach, a conceptual approach, and a case approach. The result of this study is that the legal relationship between hospitals, doctors, and patients gives birth to rights and obligations for the parties based on the therapeutic agreement that has been regulated in Article 46 of Law Number 44 of 2009 concerning Hospitals, so that patients receive legal protection due to alleged malpractice committed by medical personnel, in this case doctors with the current laws and regulations